The African enigma: The mystery of tall African adults despite low national incomes revisited - Moradi, Alexander; Hirvonen, Kalle (Oxford University Press, 2016)
African adult populations are remarkably tall for the low income levels that prevail at the country level. The average African woman is about 158.5 cm tall, whereas the low gross domestic product per capita would lead us to expect a mean height more similar to the shortest populations in the world, about 4 cm shorter. This is the case in spite of the fact that indicators of socioeconomic status and height are positively correlated within each country. The chapter also shows that the physical stature of African children fit well into the global income–height relationship. Hence, we conclude that the anomaly in the income–height nexus at country level appears to originate between childhood and adulthood. We present evidence for considerable catch-up growth involving entire populations. We discuss possible reasons for this catch-up growth including genetics, and, above all, better nutrition and health conditions during adolescence.